Analisis Keterampilan Membuka Kelas Pada Guru Pjok Di Mi Plus Ja – Alhaq Kota Bengkulu - Ogakardiansyah, Ogakardiansyah; Dewi, Citra; Sumantri, Ajis (Journal Of Dehasen Educational Review, 2024)
This study aims to determine the level of skills in opening class for PJOK teachers at Mi Plus Ja - Alhaq Bengkulu City. Descriptive Qualitative research type with research informants pjok teachers, teachers, principals and students. The results of research on the skills of opening the class of pjok teachers at MI Plus Ja-Alhaq are good as evidenced by the results of interviews and observations in this study. In the observation technique, class 1 obtained a score of 160 with a percentage of 80%, class 2 obtained a score of 161 with a percentage of 81%, class 3 obtained a score of 172 with a percentage of 86%, class 4 obtained a score of 173 with a percentage of 87%, class 5 obtained a score of 177 with a percentage of 89%, and class 6 obtained a score of 178 with a percentage of 89%. There are several aspects of the pjok teacher's skills in opening the class such as; lining up students, counting / attendance, leading prayers, giving greetings, giving apperceptions, conveying learning objectives, leading warm-ups, preparing places, preparing tools and preparing media.